학령기 지적장애아동의 이야기 이해 및 표현능력 향상을 위한 멀티미디어 앵커드 수업 프로그램의 적용 - 전혜완(Hye Wan Jeon); 박은실(Eun Sil Park) (언어치료연구, 2023)
목적: 학령기 지적장애아동의 경우 인지발달과 언어발달의 문제로 이야기를 읽은 뒤 문자와 의미의 연결 어려움을 보이며, 이야기 이해와 표현에서도 많은 어려움을 보인다. 따라서 학령기 지적장애아동의 이야기 이해 및 표현능력 향상을 위하여 멀티미디어 앵커드 수업 프로그램을 실시하여 그 효과를 살펴보고자 하였다. 방법: 연구에 참여한 대상자는 학령기 지적장애아동 6명으로 멀티미디어 앵커드 수업 프로그램의 효과를 알아보기 위하여 사전ㆍ사후설계를 적용하였다. 3명씩 소그룹으로 나누어 프로그램을 실시하였으며 중재 프로그램은 총 5단계로 구성하였다. 1단계 앵커의 제시, 2단계 앵커의 확인, 3단계 앵커의 연결, 4단계 해결책 제시, 5단계 앵커의 적용으로 진행하였다. 중재 후 이야기 이해능력과 이야기 표현능력의 변화정도를 살펴보았다. 결과: 첫째, 멀티미디어 앵커드 수업 프로그램 적용 후 사실적 정보 이해과제, 택스트 연결 추론 이해과제, 빠진 정보 추론 이해과제는 사후평가에서 높은 점수를 나타내었다. 사실적 정보 이해과제와 텍스트 연결 추론 이해과제에 대한 사전ㆍ사후평가의 점수는 통계적으로 유의한 차이를 나타내었으나 빠진 정보 추론 이해과제의 점수는 통계적으로 유의한 차이를 보이지 않았다. 둘째, T-unit, MLTw, 종속절 유형의 수, MDCTU 분석에 대한 사전ㆍ사후평가 결과 연구대상 아동들 모두 사후평가에서 높은 수치를 나타내었다. MDCTU에 대한 사전ㆍ사후평가의 수치는 통계적으로 유의한 차이를 나타내었다. 결론: 위와 같은 결과를 통해 멀티미디어 앵커드 수업 프로그램이 학령기 지적장애아동의 이야기 이해 및 표현능력에 긍정적인 영향을 미치는 것을 알 수 있다. 다만 일반화하여 해석하기에는 다소 무리가 있으므로 추후 체계적인 연구가 필요할 것으로 사료된다. Purpose: School-age children with intellectual disabilities have difficulty with cognitive and language development. These challenges cause difficulties in connecting letters and meaning and in comprehending and expressing stories. Therefore, in order to improve the story comprehension and expression ability of school-age children with intellectual disabilities, we implemented an anchored instruction program and examined its effectiveness. Methods: Six school-age children with intellectual disabilities participated in the study, and a pre-post design was applied to determine the effectiveness of the program. The program was conducted in small groups of three participants each, and the program consisted of a total of five stages. It proceeded with presentation of the anchor [1st stage], confirmation of anchors [2nd stage], connection of anchors [3rd stage], presentation of solutions [4th stage], and application of anchors [5th stage]. After the intervention, we examined the degree of change in story comprehension and expression abilities. Results: First, the tasks of comprehension of literal/factual information, text-connection inference, and gap-filling inference showed high scores in the post-evaluation. There was a statistically significant difference in the score changes in the literal/factual information and text-connection inference. Howevere, there was no statistically significant difference in the gap-filling inference. Second, T-unit, MLTw, number of dependent clause types, and MDCTU showed high values in the post-evaluation. The numerical change in MDCTU showed a statistically significant difference. Conclusions: The results show that the media anchored instruction program has a positive effect on subjects’ ability to comprehend and express stories. However, since it is somewhat difficult to generalize and interpret, it is believed that further systematic research in needed. KCI Citation Count: 0